Prototype of Automatic Control System for Water Temperature and Acidity in Ornamental Fish Aquarium Based on Internet of Things (IOT) - Adi Hermansyah; Tri Wanda Septian; Aditya Putra Perdana P; Mgs Muhammad Faris (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
The prototype application of an automatic control system in an Internet Of Things-based aquarium using DS18B20 and PH-4502C temperature sensors using the NodeMCU ESP 8266 microcontroller is a system that can regulate the temperature and pH of water automatically which is applied to a small aquarium. This technological advancement is very helpful for people who have busy daily lives who do not have time or cannot check the condition of the fish in their aquarium. To see the condition of ornamental fish aquarium can be checked from mobile phone through blynk application. Monitoring using the blynk application can be done anywhere as long as the device is always connected to the internet.